Clay-Polymer Nanocomposites Prepared by Reactive Melt Extrusion for Sustained Drug Release - Xu Liu; Xingyu Lu; Yongchao Su; Eucharist Kun; Feng Zhang (MDPI AG, 2020)
Clay−polymer nanocomposites have exhibited a great potential as carriers for controlled release drug delivery. This study aims to prepare exfoliated montmorillonite−Eudragit RS nanocomposites using reactive melt extrusion and investigate the influence of claying loading, clay types (sodium montmorillonite (Cloisite Na) vs. organomodified montmorillonite (Cloisite 20)) on clay−polymer interactions and drug release properties. The clays were used as the filler material at various levels in Eudragit RS and theophylline was used as the active pharmaceutical ingredient. The resulting structure of the nanocomposites was characterized using TEM (transmission electron microscopy) and XRPD (X-ray powder diffraction). The hygroscopicity of the nanocomposites was investigated using DVS (dynamic vapor sorption). The effect of the interfacial interaction between the polymer and clay sheet, the clay loading as well as the clay type on the drug release behavior were further studied by dissolution testing. TEM and XRPD data show that when the clay content is increased from 5% to 15% by weight, the nanocomposite’s structure switches from a fully exfoliated state to intercalated structures or partial exfoliation with stacked clay layers. FT-IR (fourier transform infrared spectroscopy) and ssNMR (solid-state NMR) results suggest that Cloisite Na and Cloisite 20 layers exhibit different interaction strengths with polymer networks by creating compacted complex structures. The addition of nanoclay in the formulation could robustly adjust drug release profiles, and the clay concentration and type are important factors that affect the crossing-linking density of the nanocomposites by adjusting the drug release properties. This study indicates that the clay−Eudragit RS nanocomposites provide an improved oral controlled drug delivery system that minimizes the drug dosing frequency, potentially leading to improved patient compliance.